Gut Microbiome Differences in Infants at High vs. Low Risk of Early Obesity. (29th May 2020) - Woo, Jessica; Ollberding, Nicholas; Crimmins, Nancy; Haslam, David
Abstract: Objectives: Fifty % of infants above the BMI 85 th percentile will develop overweight or obesity by age 6. This study aimed to evaluate differences in the gut microbial ecology of infants at high- and low-risk of developing overweight or obesity. Methods: Infants enrolled at age 6 months were classified into high-risk or low-risk based on BMI ≥85th or <85th percentile; stool samples were collected from the diaper and microbial DNA extracted. Metagenomic shotgun sequencing was performed on the Illumina HiSeq at an average depth of 15 million paired-end reads per sample. Taxonomic profiling was performed using Kraken against a custom genome database. Multiple linear regression was used to test for group differences in observed species richness and Shannon diversity, adjusted for age, delivery type, breast feeding, and introduction of solid food. Beta-diversity ordinations assessed group clustering according to species community composition. Moderated negative binomial regression using DESeq2 was used to identify differentially abundant species. Functional profiling of microbial pathways was conducted using HUMAnN2, and group differences assessed using ALDEx2. Results: Sixty-one infants (46% male, 69% black) were enrolled; 13 (21%) were high-risk. Low-risk and high-risk infants differed by race (mixed race more common in high-risk, P  = 0.02), and marginally by parent marital status and number of older children in the household (both P  = 0.06). Number of observed species were marginally higher in the high-risk group ( P  = 0.09), with no group differences in beta-diversity ordinations. Several Streptococcus, Enterobacter, Bacteroides and Lactobacillus species were more abundant in high-risk infants, while Haemophilus, Bifidobacterium and Prevotella species were more abundant in low-risk infants. High-risk infants had a more "mature" microbiome characterized by increased abundance of Ruminococcus, Blautia, and Lachnospiraceae . The PWY.5676 Acetyl-CoA fermentation to butyrate pathway was also significantly enriched in high-risk infants. Conclusions: Infants at high risk for obesity are characterized by a microbiome more abundant in species seen in older children, and with a greater functional capacity to harvest energy from complex carbohydrates. Funding Sources: Digestive Health Center Pilot Grant.